The Impact of Leadership, Employee Competence and Organizational Work Culture on Employee Performance at Bank Jatim - Nurul Qomariah; Mochamad Rochmadoni; Iqbal Rush Aviciena; Anita Eka Navalina; Nursaid Nursaid (Budapest International Research and Critics University, 2023)
Performance is an indicator of good or bad management decisions in decision making. Good or high performance can help the company make a profit, on the other hand if the performance goes down it can be detrimental to the company. This study aims to determine the effect of leadership, employee competence, and organizational culture on employee performance at Bank Jatim, Jember Branch. The research population is 54 bank employees. Questionnaires were submitted to all employees with a return rate of 41 questionnaires. This type of research is quantitative with multiple regression analysis method. The results showed that partially leadership and employee competence had a significant effect on employee performance at Bank Jatim, Jember Branch, while organizational culture had no significant effect on employee performance.